Investigating predictors of willingness to receive an HIV vaccine in a South African sample of young adults - Watson, Morgan Matshediso Roebert (Department of Psychiatry and Mental Health, 2026)
HIV continues to be a major global health challenge, leading to substantial morbidity, mortality, and economic burden. Low and middle-income countries have long borne the brunt of the global epidemic. Specifically, South Africa has the largest population of people living with HIV. Promisingly, new infections have generally decreased largely due to immense treatment-as-prevention efforts. However, HIV incidence remains an issue, especially among youth, and young woman in South Africa. Many experts believe that the addition of a protective HIV vaccine is critical in completely controlling the epidemic. However, as we have witnessed in recent years, vaccine availability does not necessarily result in public acceptance and uptake. Therefore, considering how instrumental an HIV vaccine would be in curbing HIV incidence, it is important to explore key populations- namely young adult's willingness to receive one. This quantitative study employed a cross-sectional design to investigate willingness and associated factors within a sample of young adults. Specifically, the role of socio-demographic factors, key psychological antecedents, HIV stigma, HIV knowledge, perceived risk and perceived severity of HIV were examined as potential predictors of HIV vaccine willingness. In this study 173 HIV-negative young adults between the ages of 18 and 25 were recruited through a convenience sample at two youth clinics in Khayelitsha, Cape Town. This population is characterised by high levels of HIV incidence and are likely to be targeted by initial vaccination efforts. Data were collected through facilitated face-to-face surveys in either English or isiXhosa and stored on REDCap. The statistical analyses in this study were preformed using IBM SPSS Statistics (Version 28.01, 2021). Descriptive statistics were generated for key variables, followed by inferential analyses, including Fisher's Exact Test and one-way ANOVA, to compare group means. For non-normally distributed data, non-parametric alternatives were applied. Regression analyses were conducted to assess predictors of vaccine willingness, ensuring all assumptions, such as homoscedasticity and multicollinearity, were met. The results of the study indicate that there is high willingness to receive an HIV vaccine (82.04%) amongst young adults in this sample. Furthermore, the results showed that HIV stigma, and the key psychological antecedents of collective responsibility and constraints, were significant predictors of willingness within this sample. Sociodemographic variables, HIV knowledge and perceived HIV risk and severity showed no significant association. These results suggest that public health interventions aimed at enhancing vaccine uptake should consider focusing on fostering a sense of collective responsibility while addressing HIV stigma and constraints linked to health seeking. Understanding the factors that influence willingness to receive an HIV vaccine is crucial for public health planning. The findings of this study hope to address the existing gap in the literature on young adults' attitudes towards a future HIV vaccine in South Africa